Cobalt Pincer Complexes for Catalytic Reduction of Carboxylic Acid Esters. Issue 5 (28th December 2017) - Junge, Kathrin; Wendt, Bianca; Cingolani, Andrea; Spannenberg, Anke; Wei, Zhihong; Jiao, Haijun; Beller, Matthias
Abstract: A selection of cobalt(I) and cobalt(II) pincer type complexes with different substitution patterns was tested in the catalytic reduction of carboxylic acid esters to alcohols. The cobalt pincer type complex4 is suitable for the hydrogenation of aromatic as well as aliphatic and cyclic esters. Mechanistic investigation indicated a metal ligand cooperated reaction pathway. Abstract : An efficient cobalt PNP pincer type catalyst has been developed for the catalytic reduction of carboxylic acid esters to alcohols. The cobalt pincer type complex was made that is suitable for the hydrogenation of numerous aromatic as well as aliphatic and cyclic esters. Mechanistic investigation indicated a metal ligand cooperated reaction pathway.